2023
DOI: 10.3390/ijms24065526
|View full text |Cite
|
Sign up to set email alerts
|

Advances in Cartilage Tissue Engineering Using Bioinks with Decellularized Cartilage and Three-Dimensional Printing

Abstract: Osteoarthritis, a chronic, debilitating, and painful disease, is one of the leading causes of disability and socioeconomic burden, with an estimated 250 million people affected worldwide. Currently, there is no cure for osteoarthritis and treatments for joint disease require improvements. To address the challenge of improving cartilage repair and regeneration, three-dimensional (3D) printing for tissue engineering purposes has been developed. In this review, emerging technologies are presented with an overview… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 65 publications
(252 reference statements)
1
1
0
Order By: Relevance
“…Other reports have demonstrated that the use of cartilage-derived extracellular matrix in the bioink similarly had a positive effect upon chondrocyte proliferation and ECM production [45,46]. Our findings are similar to previous studies involving bioinks with animal-derived cartilage powder [47]. Wu et al investigated a bioink made of alginate, porcine articular decellularized extracellular matrix (dECM) and stem cells from rabbit adipose tissue, and found an increase in cell aggregation and SOX9 expression [48].…”
Section: Discussionsupporting
confidence: 87%
“…Other reports have demonstrated that the use of cartilage-derived extracellular matrix in the bioink similarly had a positive effect upon chondrocyte proliferation and ECM production [45,46]. Our findings are similar to previous studies involving bioinks with animal-derived cartilage powder [47]. Wu et al investigated a bioink made of alginate, porcine articular decellularized extracellular matrix (dECM) and stem cells from rabbit adipose tissue, and found an increase in cell aggregation and SOX9 expression [48].…”
Section: Discussionsupporting
confidence: 87%
“…Hydrogels are injectable nanoscale polymeric networks made up of gelatin or collagen, with the capability to consolidate and take on the required form of the issue after embedding. When hydrogels are injected with chondrocytes, they form cartilage-like ECM with increasing mechanical improvement as a result of the ongoing formation of a glycosaminoglycan-rich matrix ( Ahmadian et al, 2023 ; Guo et al, 2023 ; Stone et al, 2023 ).…”
Section: Epidemiology: Keeping Orthopaedic Disorders In Perspectivementioning
confidence: 99%